1985
DOI: 10.1002/ajh.2830200103
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes and levels of fetal hemoglobin and Gγ to Aγ ratios in mediterranean patients with thalassemia minor and major

Abstract: This study concerned the gamma chain composition of Hb F and the haplotypes of 44 patients with beta-thalassemia major or intermedia and many of their relatives. Seventeen patients came from Northern (Turkish) Cyprus, 12 from the Istanbul area, and 15 from Macedonia and Bulgaria. Analysis of the A gamma T-G gamma-A gamma I ratio was made by HPLC, while haplotyping involved seven restriction sites. Specific haplotypes were present in certain populations; haplotype I [1] is the dominant type among North Cypriot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…On normal chromosomes 11, the alleles detected in the three families studied are: one allele associated with haplotype IX-Xmn+ and leading to high Gy values, one allele also associated with haplotype IX-XmnI + but leading to intermediary Gy values, and one allele associated with haplotype I-Xmn I and leading to low Gy values. Our assumption that normal chromosomes with haplotype IX and the Xmn I site are carrying alleles which determine relatively high Gy values fits well with the conclusions based on hemoglobinopathies study (2,3,7,8,9).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…On normal chromosomes 11, the alleles detected in the three families studied are: one allele associated with haplotype IX-Xmn+ and leading to high Gy values, one allele also associated with haplotype IX-XmnI + but leading to intermediary Gy values, and one allele associated with haplotype I-Xmn I and leading to low Gy values. Our assumption that normal chromosomes with haplotype IX and the Xmn I site are carrying alleles which determine relatively high Gy values fits well with the conclusions based on hemoglobinopathies study (2,3,7,8,9).…”
Section: Discussionsupporting
confidence: 86%
“…The Gy values observed in these 6 SS patients fell within a narrow range, with a mean value of 44% k 5 % . All 6 patients were found homozygous for the Benin haplotype ----+ + + defined by the Hinc I1 5' E , Hind I11 Gy, Hind 111 Ay, Hinc I1 ~ ( 3 , Hinc I1 3' ~( 3 , Ava I1 (3 and Bam H I 3' polymorphic restriction sites respectively (5). This haplotype is referred to as haplotype S , in the pedigrees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haplotype determination involved the following restriction sites: Hinc I1 5' to E; Xmn I 5' to "y; Hind 111 a t Gy and Hinc I1 at tjB and 3' to it: Ava I1 at 8. and Hpa I and Bam HI 3' to / 3 (Orkin et al, 1982). Methodology has been described before (Harano et al, 1985;Aksoy et al, 1985): the presence and absence of a restriction site are indicated by [ +] or [-I, respectively. The numbers of a-globin genes and possible abnormalities in the [-globin gene arrangement were determined in digests with several restriction enzymes and hybridization with a n tl probe and a 4 probe (Felice et al, 1986;Gu et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Haplotyping was done for the 4 members of the family and involved the following restriction sites: Hin cII 5′ to ε, Hin dIII at G γ and A γ, Hin cII at ψβ and 3′ to it, Ava II at β, and Bam HI 3′ to β. The methodology and probes have been listed before [23, 24]. The number of α-globin genes was determined by gene mapping with the methodology routinely in use in our laboratory [19, 25].…”
Section: Patient and Methodsmentioning
confidence: 99%